2018
DOI: 10.1021/acs.langmuir.8b02277
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Adsorption of ZrO2 Nanoparticle and Alkali Cations (Li+–Cs+) on Muscovite (001)

Abstract: We studied the adsorption behavior of ZrO nanoparticles on a muscovite (001) surface in the presence of cations from the alkali series (Li, Na, K, Rb, and Cs). The results of X-ray reflectivity, i.e., specular crystal truncation rod and resonant anomalous X-ray reflectivity in combination with AFM images, show that the sorption of ZrO nanoparticles is significantly affected by the binding mode of alkali ions on the muscovite (001) surface. From solutions containing alkali ions binding as outer sphere surface c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
2
7
1
Order By: Relevance
“…Li et al [23] reported similar problems detecting UV-Vis signals at concentrations as low as 0.05 wt%. The observations made in the batch sorption experiments attribute temperature a minor effect in adsorption behaviour do not confirm the work presented by Pham and Nguyen [34]. There, an increased nanoparticle aggregation rate at elevated temperatures was attributed to the higher kinetic energy and more frequent particle collisions.…”
Section: Discussion Of Batch Sorption Resultscontrasting
confidence: 75%
See 2 more Smart Citations
“…Li et al [23] reported similar problems detecting UV-Vis signals at concentrations as low as 0.05 wt%. The observations made in the batch sorption experiments attribute temperature a minor effect in adsorption behaviour do not confirm the work presented by Pham and Nguyen [34]. There, an increased nanoparticle aggregation rate at elevated temperatures was attributed to the higher kinetic energy and more frequent particle collisions.…”
Section: Discussion Of Batch Sorption Resultscontrasting
confidence: 75%
“…The work conducted by Pham and Nguyen [34] showed reduced adsorption in higher concentrations of nanofluid. They suggested surface modifications provide stability to the dispersion beyond a certain concentration threshold.…”
Section: Discussion Of Batch Sorption Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…As an example, Fig. 16 shows representative data and the corresponding electron densities at the mica/water interface, after reacting muscovite with Zr for 24 h in two different background electrolytes (LiCl and CsCl) (Qiu et al, 2018). The CTR-derived electron density changes abruptly at the mica surface (0 Å , defined as the position of the top-most oxygen layer in the mica structure) from the crystalline structure left to the aqueous phase right.…”
Section: Xrd-1 (Six-circle Diffractometer)mentioning
confidence: 99%
“…(b) Representative RAXR data at two values of q (dots) and best fit models (lines). (c, d) CTR-derived total electron density distributions (drawn lines) and RAXR-derived interfacial Zr electron densities (filled areas) above the mica (001) basal plane for the two media (Qiu et al, 2018).…”
Section: Xrd-2 (Pilatus Diffractometer)mentioning
confidence: 99%